2019
DOI: 10.1186/s42269-019-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adding natural bioactive mixture composed of lemon, onion, and garlic juice at different levels on productive performance, egg quality, and some blood parameters of commercial laying hens

Abstract: Background: The World Health Organization (WHO) encourages using medicinal herbs and plants to substitute or minimize the use of chemicals through the global trend to go back to nature. Many studies mentioned that using medicinal herbs and plants as feed additives seems to be a recent trend depending on availability and their cost but using them with monogastric animals and birds, as pharmaceutical tool, is available. Their action was manifested in a reduced expanding range of pathogenic microorganisms in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
8
0
1
Order By: Relevance
“…The longissimus dorsi of the rabbit carcass is one of the parts that give more weight to the carcass due to the percentage of meat present in this muscle section (Barrón et al, 2005). Similar results were obtained by Omer et al (2015) by adding a mixture of garlic, onion, and lemon extracts to rabbit feed during fattening.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The longissimus dorsi of the rabbit carcass is one of the parts that give more weight to the carcass due to the percentage of meat present in this muscle section (Barrón et al, 2005). Similar results were obtained by Omer et al (2015) by adding a mixture of garlic, onion, and lemon extracts to rabbit feed during fattening.…”
Section: Resultssupporting
confidence: 80%
“…Rabbit meat contains enough nutrients to facilitate microbial growth even at refrigeration temperatures, and has intrinsic and extrinsic factors (Koné et al, 2016); besides, the physiological status of the animal at slaughter and the ultimate pH of 6 (Nakyinsige et al, 2014) affect the microbial growth rate. Omer et al (2015) added a mixture of garlic, onion, and lemon as an additive in rabbit feed to improve the microbiological quality of the meat and demonstrated a decrease in the total viable count; likewise, Mancini et al (2016) reported a lower total bacterial count in rabbit burger patties supplemented with turmeric powder and ascorbic acid at day 0 of storage in refrigeration. Koné et al (2016) reported a lower concentration of mesophilic bacteria in the meat of rabbits fed with plant extracts and essential oils, stored under refrigeration and aerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…As porcentagens de albúmen e gema estão dentro do esperado para galinhas poedeiras de 55 semanas de idade e corroboram os resultados encontrados em outros estudos (Omer et al, 2019;Seidavi et al, 2020). Alguns estudos apontam diferentes resultados no uso de plantas fitogênicas na alimentação das aves.…”
Section: Discussionunclassified
“…Antibiotics have commonly been used as growth promoters (1) However, to meet regulations requirements, organic poultry systems avoid using antibiotics and tend to replace them with natural additives. Studies have shown that natural additives could be a better substitute for antibiotic additives in broilers (2) as well as in laying hens (3) . Using plant-based additives presents numerous advantages, including safety for birds, humans, and the environment; limiting drug resistance, and diminishing antibiotic residues in poultry products (4) .…”
Section: Introductionmentioning
confidence: 99%